Repair of a Strip Perforation with Calcium-Enriched Mixture Cement: A Case Report - Eghbal, Mohammad Jafar; Fazlyab, Mahta; Asgary, Saeed (Iranian Endodontic Journal, 2014)
The present report reviews the diagnostic and treatment challenges of a mandibular molar with previous root canal treatment and signs of a procedural mishap, i.e. furcal radiolucency and localized swelling of the gingival margin in which a sinus tract was present. By tracing the sinus tract, it became evident that the lesion originated from the furcation area, not the root apices. This case was treated by cleaning/filling the coronal half of the canals and leaving the rest of obturating material in situ. The strip perforation zone in the mesial root was sealed off with calcium-enriched mixture cement. One-week post-operative, patient’s symptoms faded away and after one year, the lesion completely healed with bone replacement.